Development of a basic technical learning model for long jump squat style based on traditional games for students - Almen, Almen; Dewi, Muharika (PT The Collaboration UVW, 2024)
This research aimed to develop a learning model for basic long jump techniques based on traditional games. This research’s subjects were the students of SMAN 1 Pulau Punjung, Dharmasraya Regency. The research method used model development research, Borg and Gall. The data collection techniques used the results of expert validation and tests effectiveness through experiments with statistical data analysis paired t-test. The results of research and development of a traditional game-based learning model for basic long jump techniques in squatting style for students at SMAN 1 Pulau Punjung showed that the learning model for basic long jump techniques in squatting style based on traditional games is suitable for students. The results of the effectiveness test showed that the traditional game-based long jump technique learning model was effective for students of SMAN 1 Pulau Punjung, this was demonstrated by the results of the T-Test and N-Gain Score on the basic technical abilities of the traditional game-based squat style long jump which showed significant improvement.